Iatrogenic pyriform sinus perforation during endoscopic ultrasonography - Young Min Kim; Jae Jun Park; Young Hoon Youn (International Journal of Gastrointestinal Intervention, 2019)
Summary of Event A 65-year-old women underwent endoscopic ultrasonography (EUS) to evaluate the gastric submucosal tumor. The EUS scope was inserted into the esophagus after two attempts. A neck computed tomography (CT) scan showed a pneumomediastinum and an air bubble deep in the neck, suggesting an esophageal rupture. The patient was hospitalized and maintained conservative treatment including broad-spectrum antibiotics and withholding oral feeding.